Environmental impacts of seaweed cultivation: kelp farming and preservation - Thomas, Jean-Baptiste (Burleigh Dodds Series in Agricultural Science, 2021)
This chapter provides an overview of the environmental impacts of the supply chain for preserved seaweed. The supply chain includes the hatchery, marine infrastructure, deployment of juveniles and monitoring during cultivation (grow-out of seaweed), harvest, transport back to shore and preservation of the biomass. The chapter starts with a short overview of the life cycle assessment (LCA) methodology, and how it can be used to quantify the environmental impacts of seaweed supply chains. After a discussion of the overall environmental impacts of the preserved seaweed supply chain, the chapter focuses on specific life cycle stages: spore preparation and seeding of juvenile seaweed onto string in the hatchery, seaweed cultivation, harvesting preservation and storage of harvested seaweed. The chapter ends with a summary and discussion of future trends in the subject.